2013
DOI: 10.33899/rjs.2013.77817
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Spectrophotometric Determination of Thiamine Hydrochloride in Presence of Sulphite Via Chromium-1,5-Diphenylcarbazide Complex

Abstract: A simple, rapid, accurate and precise spectrophotometric method is proposed for the determination of thiamine hydrochloride (Vitamin B 1) in both pure form and in its pharmaceutical formulations. The method is based on the oxidation-reduction reaction between vitamin B 1 and known amount of chromate CrO 4-2 in acidic medium of 2N H 2 SO 4. Then, the excess of chromate is measured via 1,5-diphenylcarbazide which gives a pinkish-violet, water soluble and stable complex and exhibits maximum absorption at 543 nm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The bleaching method was applied for determination of Sulphite in various water samples, so that (1-7) mL were added to volumetric flasks containing different concentrations of Sulphite (5-100) µg/25ml , then measured the absorption at the chosen wavelength as shown in Table 5. [33] for 5 degrees of freedom at the confidence level (95%) did not exceed theoretical values when the present method was compared with the literature method [34]as it was tabulated in Table 6.…”
Section: Application Of the Present Methodmentioning
confidence: 86%
“…The bleaching method was applied for determination of Sulphite in various water samples, so that (1-7) mL were added to volumetric flasks containing different concentrations of Sulphite (5-100) µg/25ml , then measured the absorption at the chosen wavelength as shown in Table 5. [33] for 5 degrees of freedom at the confidence level (95%) did not exceed theoretical values when the present method was compared with the literature method [34]as it was tabulated in Table 6.…”
Section: Application Of the Present Methodmentioning
confidence: 86%
“…A literature review showed that very few analytical methods have been reported for optimization of spectroscopy conditions in UV-visible Spectrophotometry methods using two-level full factorial design [8] Central Composite Face Centered Design [9] Box-Behnken design [10]. A few UV-visible Spectrophotometry methods have been formerly reported for the estimation of Thiamine Hydrochloride in pharmaceuticals [11][12][13][14]. Other techniques reported for the assay of Thiamine Hydrochloride in pharmaceuticals include Fluorimetry [15,16], HPLC [17][18][19][20][21][22], Polarography method [23,24] and Voltammetry [25].…”
Section: Introductionmentioning
confidence: 99%